Explaining regionalization of trade in Asia Pacific: A transaction cost approach - Torsten Amelung (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1990)
Recent investigations on the regional distribution of trade flows in the Asia Pacific area suggest that some countries have developed strong bilateral trade links, while others obviously tend to be more closely linked towards trading partners outside the Asia Pacific area (Amelung (1990)). Moreover, empirical findings indicate that there are groups (clusters) of countries in the Asia Pacific area which - in relative terms - trade more intensively with the members of their group than with other countries of this area or the world. For instance, in the eighties there was a clear separation between a South East Asian group of trading partners comprising Singapore, Indonesia, Malaysia and Thailand and a group of North East Asian countries encompassing Korea, Taiwan, Japan, China, Hong Kong and the USA as a non-Asian nation. However, the cluster analysis does not explain why this pattern of regionalization emerges. In economic theory the regionalization of trade flows has been attributed to the. discrimination of countries through legal (El-Agraa (1988), Nienhaus (1987), p. 84) and natural trade barriers (Langhammer (1983), Deardorff (1987)). Following Viner's custom unions theory (Viner (1950)) a group of countries can negotiate preferential tariff treatment for their members, thus discriminating against non-member countries. Given such an institutional arrangement regional trade is expected to rise as a consequence of trade creation and trade diversion. Moreover, regionalization of trade flows can be enhanced by differences in transport costs resulting from the spatial remoteness of trading partners. As Deardorff shows, these differentials may affect both the direction and the composition of trade, since they constitute natural trade barriers.
Keywords: 330; Transaktionskosten; Asiatisch-pazifischer Raum; Außenwirtschaft